Identifying barriers to hepatocellular carcinoma surveillance in a national sample of patients with cirrhosis. Issue 3 (5th October 2016) - Goldberg, David S.; Taddei, Tamar H.; Serper, Marina; Mehta, Rajni; Dieperink, Eric; Aytaman, Ayse; Baytarian, Michelle; Fox, Rena; Hunt, Kristel; Pedrosa, Marcos; Pocha, Christine; Valderrama, Adriana; et al.
Abstract : Hepatocellular carcinoma (HCC) is a leading cause of morbidity and mortality in cirrhosis patients. This provides an opportunity to target the highest‐risk population, yet surveillance rates in the United States and Europe range from 10% to 40%. The goal of this study was to identify barriers to HCC surveillance, using data from the Veterans Health Administration, the largest provider of liver‐related health care in the United States. We included all patients 75 years of age or younger who were diagnosed with cirrhosis from January 1, 2008, until December 31, 2010. The primary outcome was a continuous measure of the percentage of time up‐to‐date with HCC surveillance (PTUDS) based on abdominal ultrasound (secondary outcomes included computed tomography and magnetic resonance imaging). Among 26, 577 patients with cirrhosis (median follow‐up = 4.7 years), the mean PTUDS was 17.8 ± 21.5% (ultrasounds) and 23.3 ± 24.1% when any liver imaging modality was included. The strongest predictor of increased PTUDS was the number of visits to a specialist (gastroenterologist/hepatologist and/or infectious diseases) in the first year after cirrhosis diagnosis; the association between visits to a primary care physician and increasing surveillance was very small. Increasing distance to the closest Veterans Administration center was associated with decreased PTUDS. There was an inverse association between ultrasound lead time (difference between the date an ultrasound was ordered and requested exam date) and the odds of it being performed: odds ratio = 0.77, 95% confidence interval 0.72‐0.82 when ordered > 180 days ahead of time; odds ratio = 0.90, 95% confidence interval 0.85‐0.94 if lead time 91‐180 days. Conclusions : The responsibility for suboptimal surveillance rests with patients, providers, and the overall health care system; several measures can be implemented to potentially increase HCC surveillance, including increasing patient–specialist visits and minimizing appointment lead time. (Hepatology 2017;65:864‐874).